Synthesis of Oxacycles Employing the Oxa-Pictet–Spengler Reaction: Recent Developments and New Prospects - Larghi, Enrique Leandro (2011)
The oxa-Pictet-Spengler cyclization is the oxygen variation of the Pictet-Spengler reaction, in which an aromatic alcohol component (generally a β-arylethyl alcohol) reacts with acarbonyl component (aldehyde, ketone or their masked derivatives), to yield a 1-substituted (or 1,1′- disubstituted)pyran fused to the aromatic ring system found in the starting alcohol. The transformation is usually promoted by Brønsted and Lewis acids. Intramolecular versions of the reaction are also known, where both components are mutually masked as an acetal. Discussed here are aspects concerning the most recent developments and new applications of this useful reaction, including the scope and limitations of new promoters, and new mechanistic pictures of this transformation. The use of novel stereochemical control strategies and the application of the reaction to the synthesis of natural products and their analogs, as well as to accessing fully synthetic bioactive compounds and new ring systems are presented, and chiral versions of the oxa-Pictet-Spengler are also analyzed.